2020
DOI: 10.1097/tp.0000000000003335
|View full text |Cite
|
Sign up to set email alerts
|

Donor Hepatectomy and Implantation Time Are Associated With Early Complications After Liver Transplantation: A Single-center Retrospective Study

Abstract: Jochmans are recipients of a CAF chair for abdominal transplant surgery. J. Pirenne is recipient of an IGL chair for abdominal transplant surgery. D. Monbaliu is a senior researcher of the research foundation Flanders (Fonds Wetenschappelijk Onderzoek -Vlaanderen, FWO), Belgium. The department of abdominal transplant surgery has received unrestricted grants from Astellas and Roche.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 21 publications
(50 reference statements)
2
42
2
Order By: Relevance
“…Nevertheless, the inverse probability of treatment weighting approach has accounted for baseline differences of these parameters sufficiently, allowing us to compare LTx with comparable duration of these surgical times (Table S3), thereby reducing their confounding effect. Furthermore, a recently performed retrospective analysis investigating the effect of donor hepatectomy and liver implantation time on the probability to develop EAD [23] showed that HTK is associated with the probability of this complication independently from the effect of all abovementioned surgical times, consistent with the findings reported herein.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the inverse probability of treatment weighting approach has accounted for baseline differences of these parameters sufficiently, allowing us to compare LTx with comparable duration of these surgical times (Table S3), thereby reducing their confounding effect. Furthermore, a recently performed retrospective analysis investigating the effect of donor hepatectomy and liver implantation time on the probability to develop EAD [23] showed that HTK is associated with the probability of this complication independently from the effect of all abovementioned surgical times, consistent with the findings reported herein.…”
Section: Discussionsupporting
confidence: 89%
“…Adelmann et al showed an independent correlation between donor hepatectomy time in DBD and early graft function measured by the Model for Early Allograft Function score 22 . In our cohort, the risk of early allograft dysfunction was not influenced by donor hepatectomy time 23 . However, the odds of ischemic cholangiopathy increased by 19% per 10‐min increase in donor hepatectomy time 23 .…”
Section: Livermentioning
confidence: 45%
“…In our cohort, the risk of early allograft dysfunction was not influenced by donor hepatectomy time 23 . However, the odds of ischemic cholangiopathy increased by 19% per 10‐min increase in donor hepatectomy time 23 . Our Eurotransplant registry study showed donor hepatectomy time to be an independent predictor of overall graft failure 24 .…”
Section: Livermentioning
confidence: 54%
See 2 more Smart Citations